2013
DOI: 10.1128/aem.01193-13
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Predation and Biofilm Formation under Different Ambient Oxygen Conditions Using a Simple Gasbag-Based System

Abstract: Bdellovibrio bacteriovorus and Micavibrio aeruginosavorus are Gram-negative bacteria characterized by predatory behavior. The aim of this study was to evaluate the ability of the predators to prey in different oxygen environments. When placed on an orbital shaker, a positive association between the rate of aeration and predation was observed. To further examine the effects of elevated ambient oxygen levels on predation, a simple gasbag system was developed. Using the system, we were able to conduct experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…Data obtained from single and dual cultures showed that the biofilm-producing ability was markedly higher under aerobic atmospheres. Kadouri and Tran (2013) measured biofilm formation by a variety of opportunistic pathogens, at different oxygen concentrations, and also established a positive correlation between oxygen levels and biofilm formation ability. Data also suggested that the changes in the overall biofilm mass and culturable cells of dual biofilms can be due to reciprocal interference between species in the consortia or even only triggered by P. aeruginosa .…”
Section: Discussionmentioning
confidence: 89%
“…Data obtained from single and dual cultures showed that the biofilm-producing ability was markedly higher under aerobic atmospheres. Kadouri and Tran (2013) measured biofilm formation by a variety of opportunistic pathogens, at different oxygen concentrations, and also established a positive correlation between oxygen levels and biofilm formation ability. Data also suggested that the changes in the overall biofilm mass and culturable cells of dual biofilms can be due to reciprocal interference between species in the consortia or even only triggered by P. aeruginosa .…”
Section: Discussionmentioning
confidence: 89%
“…It has even been suggested that B. bacteriovorus may contribute to health as part of the human gut microbiota (Iebba et al, 2013). Although considered as obligately aerobic bacteria, research has shown that BALOs can survive under anoxic conditions and that certain strains, including B. bacteriovorus, are able to grow and attack under microaerobic conditions (Kadouri and Tran, 2013;Patini et al, 2019). These findings further support the potential of using these predators as therapeutics in environments such as the gastrointestinal tracts (Sockett and Lambert, 2004;Dwidar et al, 2012b).…”
mentioning
confidence: 81%
“…The level of oxygen is proven to be critical for B. bacteriovorus ability to prey upon cells. While maintaining the ability to reduce biofilms, lack of oxygen inhibits any predation upon planktonic cells (Kadouri and Tran, 2013;Patini et al, 2019).…”
Section: Potential Limitationsmentioning
confidence: 99%
“…They typically have a broad prey range but are unable to attack Gram‐positive or eukaryotic cells in co‐cultures, making them and/or their lytic enzymes candidates for use as biological antimicrobials against Gram‐negative bacterial pathogens (Sockett and Lambert, ; Markelova, ; Dashiff and Kadouri, ; Kadouri et al ., ). The ability of Bdellovibrio bacteriovorus to disrupt biofilms formed by Gram‐negative bacteria (Kadouri and O'Toole, ; Van Essche et al ., ; Dwidar et al ., ; Kadouri and Tran, ; Chanyi and Koval, ) adds to the potential therapeutic use of BALOs. Interestingly, a recent study by Monnappa et al .…”
Section: Introductionmentioning
confidence: 99%
“…They typically have a broad prey range but are unable to attack Gram-positive or eukaryotic cells in co-cultures, making them and/or their lytic enzymes candidates for use as biological antimicrobials against Gram-negative bacterial pathogens (Sockett and Lambert, 2004;Markelova, 2010;. The ability of Bdellovibrio bacteriovorus to disrupt biofilms formed by Gramnegative bacteria (Kadouri and O'Toole, 2005;Van Essche et al, 2009;Dwidar et al, 2012;Kadouri and Tran, 2013;Chanyi and Koval, 2014) adds to the potential therapeutic use of BALOs. Interestingly, a recent study by Monnappa et al (2014) showed that extracellular proteases from a host(prey)-independent strain of B. bacteriovorus HD100 inhibited the formation of a biofilm by the Gram-positive pathogen Staphylococcus aureus and, thus, its virulence.…”
Section: Introductionmentioning
confidence: 99%